PERBANDINGAN PROFIL LIPID DARAH PADAPASIEN STROKE ISKEMIK DAN STROKE HEMORAGIK DI RSUP FATMAWATI TAHUN 2018 - Radya Agna Nugraha (2019)
Stroke is a clinical manifestation that develops rapidly due to focal or global disruption in the brain with symptoms that last for 24 hours or more and may cause death. Lipid profile abnormalities is one of the risk factors for stroke. This research was done to compare the profile of lipid in patients with ischemic stroke and hemorrhagic stroke. This research is analytic observational with the design of crosssectional. The sample is a medical records data amounting to 201 samples. Patients with ischemic stroke in total of 106 samples and hemorrhagic stroke in total of 95 samples. The research was done in RSUP Fatmawati. The technique of sampling was done in consecutive sampling. Based on the age range, the case of ischemic stroke in this research mostly found at the age range of 55-65 years (36,8%) and >65 years old (36,8%), and hemorrhage stroke in 45-55 years (37.9%). Based on sex, men have the highest prevalence of both ischemic and hemorrhagic strokes, with a prevalence of ischemic stroke in 59 cases (55.7%) and hemorrhage in 50 patients (52.6%). Mann-Whitney U test results showed that there were significant differences in total cholesterol levels in patients with ischemic stroke compared with hemorrhagic stroke (p <0.001). This also corresponds to HDL cholesterol (p <0.001), LDL cholesterol (p <0.001), and triglycerides showed a significant difference (p <0.001). There are significant differences in total cholesterol, HDL cholesterol, LDL cholesterol, and triglycerides in patients with ischemic stroke compared with hemorrhagic stroke.